Pengaruh Brand Image Produk Private Label Terhadap Kepuasan Pelanggan - Isyatin Amalianti; Ermina Tiorida (Jurnal Riset Bisnis dan Investasi, 2017)
The purpose of this research is to analyze how the influence of brand image on customer satisfaction. This research uses quantitave descriptive method. The sample in this study was 112 consumer of private label products (YOA) in Griya Supermarket Bandung, using non-probability sampling - judgement sampling. The collection of information in this study was conducted by providing questionnaires to consumers and analyzed by using descriptive analysis, correlation, regression, coefficient of determination, and hypothesis testing. The results of this study indicate that the brand image affects customer satisfaction by 15% and the rest is influenced by other factors. Analysis results show that brand image has a positive effect on customer satisfaction.